Synthesis of 2-(Indol-3-yl)-ethanone-based Arylhydrocarbon Receptor Agonist Candidates via Weinreb Amides of Indole-3-acetic Acid. - Opietnik, Martina; Jungbauer, Alois; Mereiter, Kurt; Rosenau, Thomas (Current Organic Synthesis, 2013)
Grignard reactions with the Weinreb amide (N-methoxy-N-methylamide) of indole-3-acetic acid provide a facile access to indol- 3-yl ketones, which are potential agonists of the human aryl hydrocarbon receptor (
Keywords: (3-indolyl)methyl ketones